Doubling farmers' income by 2022: pathway and strategies for wheat producers - Singh, G. P.; R., Sendhil; Kumar, Anuj; Singh, Satyavir; Tripathi, S. C. (Indian Farming, 2018)
The ambition of the Governmentof India has to be met coherentlythrough productivity enhancementcoupled with cost reduction, pricerealization and policy support.Income from a single crop orcommodity will not fulfil the targetof doubling farmers’ income but ithas to emulate from farm and nonfarmsources. Diversification ofactivities which yields betterremuneration (region specific) shouldbe the ideal strategy. Clearly, in thecase of wheat, the whole value chainhas to be strengthened to be on thetrack of doubling the income for allclasses of farmers.